If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(2x + 1) = -3x + 7 + -9x Reorder the terms: -6(1 + 2x) = -3x + 7 + -9x (1 * -6 + 2x * -6) = -3x + 7 + -9x (-6 + -12x) = -3x + 7 + -9x Reorder the terms: -6 + -12x = 7 + -3x + -9x Combine like terms: -3x + -9x = -12x -6 + -12x = 7 + -12x Add '12x' to each side of the equation. -6 + -12x + 12x = 7 + -12x + 12x Combine like terms: -12x + 12x = 0 -6 + 0 = 7 + -12x + 12x -6 = 7 + -12x + 12x Combine like terms: -12x + 12x = 0 -6 = 7 + 0 -6 = 7 Solving -6 = 7 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -3(2x+1)-5=10 | | 5(4r+2)=2(10r+5) | | 2x+8=4(x+6) | | 5s-2t+7s-9t= | | .3+4x=3x+6 | | -19(-4h-7k+5)= | | 6m-4+6m=-16 | | -3/5=y-1/2 | | (-9*6)+-4= | | 2(6x+130)=5x+164 | | 7(m+7)=40-2m | | 9y+9=15 | | X+x1/2x+1/2x=360 | | (6+2a)=1/2(4a-6) | | 4w-3w+2w+8=-16 | | 5x+6(x+10)=170 | | 15=2a-5a | | n/6=n/2-7/3 | | -4p+4=12 | | 21=-x+4x+9 | | (9*6)+-4= | | 6x-5x=4 | | -9(n-12)=3(1+8n)-12n | | x=40/(x+6) | | y=2x^3-3x^2-36x | | (4/a-2)+(5/a+2)=(5/a^2-4) | | b-5/4=b+2/3 | | -13=3-2x-4 | | -8x(.09)x(-.5)= | | -110=-5x | | 6r-7(4r+2)=28-8r | | 10+5x-7=8x+8-3x |